Diphteria - Baiq Ikatria Aisya Azzahra; Firza Padila Salsabila Al-Khatib; Ni Kadek Putri Arini Dwi Ananda; Baiq Mutiara Saji Candrawati (International Journal of Public Health Excellence (IJPHE), 2026)
Diphtheria remains a significant public health threat in Indonesia despite decades of immunization programs. The country has witnessed a resurgence of cases, with outbreaks repeatedly occurring in provinces with low vaccination coverage. While quantitative surveillance data exist, little is known about the underlying socio-behavioral and health system factors that perpetuate transmission. This qualitative study aimed to comprehensively explore the barriers to diphtheria prevention and control from the perspectives of multiple stakeholders. Using a descriptive exploratory design, in-depth interviews and focus group discussions were conducted with 60 participants, including healthcare workers, parents, community leaders, and district health officials, across three high-incidence districts. Data were analyzed thematically using Braun and Clarke’s framework. Four overarching themes emerged: (1) pervasive immunization gaps driven by vaccine hesitancy and access deficits; (2) fragmented health system capacity, particularly in surveillance and case management; (3) deeply rooted socio-cultural beliefs and misinformation; and (4) weak intersectoral coordination during outbreak response. Participants vividly described how religious objections, fear of adverse events, geographic remoteness, and inadequate logistics chain interact to sustain outbreaks. The findings highlight that diphtheria resurgence is a multifactorial phenomenon requiring integrated interventions. Strengthening routine immunization through community engagement, enhancing diagnostic capacity, and establishing culturally sensitive communication strategies are critical. This study provides essential evidence for policy refinement toward achieving diphtheria elimination in Indonesia